2015
DOI: 10.1093/fampra/cmv057
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Indonesian general practitioners in maintaining standards of medical practice at a time of health reform

Abstract: The findings indicate that a major revision of current health care system is required with a focus on promoting the concept of PHC services to the population, redefining the role of the GP to deliver recognised best practice within available resources, changing the way GPs are remunerated by the public health system and the health insurance industry, policing of the regulations related to the scope of practice of other health care professionals, particularly midwives and nurses, and regulation of prescribing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Their less positive attitude was likely related to a perception that gatekeeping formed an additional burden in their daily duties. A study in Indonesia has found that GPs perceive increasing demand from patients as one of the barriers to performing optimally as primary care physicians [10]. Moreover, it has been reported that patients perceive the quality of primary care as low and that they view the gatekeeper as an access barrier to more advanced services perceived to be of higher quality [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their less positive attitude was likely related to a perception that gatekeeping formed an additional burden in their daily duties. A study in Indonesia has found that GPs perceive increasing demand from patients as one of the barriers to performing optimally as primary care physicians [10]. Moreover, it has been reported that patients perceive the quality of primary care as low and that they view the gatekeeper as an access barrier to more advanced services perceived to be of higher quality [7].…”
Section: Discussionmentioning
confidence: 99%
“…Perceiving primary care to be of low quality, urban patients often request direct referral to secondary care facilities [7]. Currently, the strict regulations applying to NHI bene ciaries for accessing healthcare curtail such swift referrals and lead to more tension in physician-patient relationships [10,26]. Such frequent con icts may generate additional stress for GPs, thereby inducing more negative attitudes towards the gatekeeping function.…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of health insurance/Asuransi Kesehatan (ASKES) (low coverage and fragmented health insurance system) into BPJS Kesehatan (universal coverage) since 5 years ago does not significantly improve the performance and satisfaction of GPs in managing the NCDs patients because the BPJS Kesehatan implements policies which are similar to ASKES era in terms of insurance company's lack of respect for professional autonomy of the GPs. The GPs perceived that they were controlled and constrained by the health insurance policies in their clinical decision-making process and patient management strategies 3 . Policies implemented by health insurance companies should be in line with professional autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a more extensive public information campaign in television, radio, or at any community meetings is essential so that people can understand what is JKN, what is covered, what is not covered, and what are the GPs’ roles in the JKN scheme. While the literature showed that GPs also felt overwhelmed with the JKN working load [44], an insurance specialist may also help to inform the patients about any JKN regulation changes at the clinics settings.…”
Section: Discussionmentioning
confidence: 99%